The People’s Religious Republic According to Ayatullah Jawadi Àmuli - Mansur MirAhmadi (حکمت اسرا, 2011)
Many interpretations have been offered with regard to the term mardumsalariyedini (lit. “the people’s religious rule/republic”) or “religious democracy”. In some of these interpretations, the concept has been elucidated as a compound matter in the form of democracy; in other interpretations, it is likened to a simple and monolithic concept. AyatullahJawadi Àmuli’s understanding of this termcorresponds to the second type—i.e., he does not consider the concept as a mixture of religion and democracy; rather, he views it as one possessing a unified nature deriving from religion itself.Through an examination of his works, this article seeks to ascertain the views of Ayatullah Jawadi Àmuli regarding the term“the people’s religious republic”. By focussing on concepts such as existence, revelation, the intellect, man, and society—which compose the most important concepts in his analytic and conceptual framework—his views on “the people’s religious republic”are reconstructed and presented in a methodical manner.MardumsÁlÁriyedini is a model of a politic which is formally identified in the following way: it is based on the subservience of society within the threshold of the Divine; it subsists in the framework of divine guidance and religious institutions; andit is in line with the rational management of people and their governance.